Fungal endophytes: The hidden helpers in sustainable agriculture - Bhullar, Muskan (International Journal of Sustainable Agricultural Research, 2025)
Endophytes are becoming increasingly popular as a means of enhancing agricultural productivity, and they are seen as an important aspect in sustainable agriculture. These beneficial fungi form symbiotic relationships with plants, enhancing their growth, health, and resilience. Endophytes improve soil fertility by solubilizing minerals, fixing nitrogen, and producing plant growth-promoting substances. They also confer drought tolerance, disease resistance, and pest control, reducing the need for chemical inputs. Additionally, endophytes promote soil biodiversity, structure, and carbon sequestration, contributing to ecosystem services. Fungal endophytes residing symbiotically inside the plant tissues play an important role in the growth promotion and resistance to various biotic and abiotic stresses and diseases in plants. Endophytic fungi stimulate plant growth, lower oxidative stress, increase nutrient uptake, and alter levels of various phytohormones in plants grown in stressed conditions. Endophytic fungi are used as the most common microbial biological control agents (MBCAs) against various phytopathogens in the form of enhanced plant growth and induced systemic resistance, produce a variety of antifungal secondary metabolites (lipopeptides, antibiotics and enzymes) through colonization. By harnessing endophytes, we can develop innovative, eco-friendly solutions for sustainable food production, mitigating environmental impacts, and ensuring food security for future generations.